Lion Rampant - Woollcombe, Robert (London Chatto & Windus, 1955)
This memoir is an account of the experiences of a front-line infantry officer with the King's Own Scottish Borderers during the desperate battle for Normandy and the Allied advance in 1944-45. It evokes the confusion, horror and comradeship of war - from the killing fields of the Normandy bocage, through house-to-house fighting in shattered Flemish towns, to the final Rhine crossing. The story tells how the author, his fellow officers and the men of his company lived through one of the bitterest compaigns in history.
Keywords: Regimental Histories -- Great Britain